Estudio de factibilidad para la creación de una empresa de consultoría especializada en la reinserción laboral de profesionales mayores de 35 años - Bistolfi Daga, Silvana Gina (2019)
Through investigations compiled by other authors, and also from the studies conducted by the author of the present study, there is clear discrimination in selecting personnel for people over 35 years of age, which was validated with the surveys and interviews conducted that demonstrated that people currently are not being hired for an age issue, and if they would be interested in having a consulting company to advise them to get a job worthy of them or them, regardless of age. According to the revised, companies are not opting to hire people over 35 years of age, first because they believe they will charge more for the position than a young executive; second, because they believe that they adapt more slowly to changes, and third, because they believe that they are not updated with the technological demands of today…..